Ajman University students’ perspectives on university social responsibility: A field study - Nagwa Babiker, Abdalla Yousif (Opción, 2019)
The aim of the study is to investigate Ajman university students’perspectives on university social responsibility via a descriptivemethodological approach, analyzing secondary data collated fromselected existing Literature on USR that were related to the concept,origins, importance, and constraints of implementing of USRpractices. The results indicate the extent to which students, as internalstakeholders, are aware of the USR, opportunities for its improvement,and its future challenges. In conclusion, no relationship existedbetween students’ academic grades and the USR and its role in theprocess of teaching, learning and dissemination of knowledge and theteaching of good citizenship.